VISUALISASI DASHBOARD TREND KEMISKINAN KOTA DEPOK TAHUN 2021-2022 DENGAN MENGGUNAKAN MICROSOFT POWER BUSINESS INTELLIGENCE DAN METODE UAT (USER ACCEPTANCE) - Widyati Cahya Putri; Muhammad Edy Supriyadi (Jurnal Teknik dan Science, 2024)
The problem of poverty is a complex and multidimensional problem so it is a development priority for the Indonesian Government. Efforts to eradicate poverty are carried out to realize the nation's ideals, namely, the creation of a just and prosperous society. The Urban Poverty Alleviation Program (P2KP) is a national program implemented by the Indonesian Government in order to overcome the problem of poverty that occurs in society, especially people living in urban areas. The level of poverty in the city of Depok which is explained in written form is less effective and difficult for readers to understand. Therefore, this data visualization dashboard was created by the author to help readers understand the state of poverty levels in the city of Depok through several existing factors. The dashboard consists of several visuals to differentiate poverty factors. Based on tests that have been carried out using UAT (User Acceptance Testing) to determine the reader's assessment of the data visualization dashboard that has been created by distributing questionnaires to 50 respondents, resulting in a score of 82.5% which results in a "very strong" category for the Percentage Level data visualization dashboard. Depok City Poverty 2021-2022.